2015
DOI: 10.1093/ntr/ntv197
|View full text |Cite
|
Sign up to set email alerts
|

Recall and Effectiveness of Messages Promoting Smoke-Free Policies in Rural Communities

Abstract: Rural communities are disproportionately affected by SHS and less likely to be protected by smoke-free policies. This study adds evidence-based guidance for tailoring rural smoke-free media campaigns using different framing: gain-framed messages (ie, benefits of smoke-free environments) to promote recall and loss-framed content (ie, dangers of SHS) to prompt emotion. Further, gain-framed messages that are localized to the rural community may be especially effective. Findings support designing smoke-free campai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…While around a quarter (7 of 30) of mass media studies in the 2014 review evaluated local-level campaigns, only one such study was identified in 2019. 55 The reverse pattern was seen in relation to sales and marketing controls, where three studies 57 60 68 of local/voluntary sales bans were found for 2013–2018 compared with none previously. In relation to voluntary smoke-free policies, the emphasis shifted from the workplace to multi-unit housing, with three studies assessing owner restrictions on smoking in such accommodation.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…While around a quarter (7 of 30) of mass media studies in the 2014 review evaluated local-level campaigns, only one such study was identified in 2019. 55 The reverse pattern was seen in relation to sales and marketing controls, where three studies 57 60 68 of local/voluntary sales bans were found for 2013–2018 compared with none previously. In relation to voluntary smoke-free policies, the emphasis shifted from the workplace to multi-unit housing, with three studies assessing owner restrictions on smoking in such accommodation.…”
Section: Resultsmentioning
confidence: 94%
“… 37 39 40 44 Where previously studies of mass media campaigns were split between those looking to boost quit intentions/attempts and those looking to increase uptake of cessation support, in the current review studies also began to examine the adoption of smoke-free homes. 35 51 Comparisons of different forms of campaign content became more common, with Durkin et al 49 and Nonnemaker et al 54 exploring the role of emotion, Kim et al 50 looking at the use of stigmatising (vs non-stigmatising) messages, and Rayens et al 55 comparing the equity impact of loss-framed and gain-framed content. The majority of mass media studies across both reviews focused on traditional media platforms such as TV and radio.…”
Section: Resultsmentioning
confidence: 99%
“…Messages that target the dangers of SHS or that highlight the benefits of smoke-free air, and those that are localized to the rural community, have a potential role in educating and promoting smoke-free workplace policies in rural areas. The authors call for additional research to determine the message framing needed to move rural residents to act (Rayens et al, 2016). Also, print advertisement messaging focusing on faith-based messaging and social norms may support smoke-free policies in rural areas, although this needs to be studied further for applicability to other rural residents (Kostygina, Hahn, & Rayens, 2014).…”
Section: Best Practices In Tobacco Control: Smoke-free Policies and Tmentioning
confidence: 99%
“…Tobacco company advertising is sophisticated, but research has shown that equally sophisticated and nuanced counteradvertising can combat industry influence in rural areas. A variety of ad types, framing strategies, and media are needed to be most effective (Rayens et al, 2016; Riker et al, 2015).…”
Section: Rural Tobacco Use and Tobacco Industry Marketingmentioning
confidence: 99%
“…En línea con los descubrimientos de Mostafa et al (2018), nuestro trabajo sostiene que los anuncios con apelaciones negativas provocan un recuerdo más sólido en la mente de los espectadores. Concretamente, en sujetos con mayor preocupación por el medio, los mensajes con valencia negativa son mejor recordados, estos hallazgos están en línea con el trabajo de (Rayens et al, 2016) en el que los sujetos con mayor conciencia del riesgo recuerdan un mayor porcentaje de anuncios con marco de pérdida. Además, coinciden con los alcanzados por Varan et al (2015) que demostraron que los consumidores recuerdan anuncios de marcas que están menos dispuestos comprar.…”
Section: Recuerdo De Los Mensajes Según Nivel De Preocupaciónunclassified